Storyboard in Teaching Writing Narrative Text - Hasan, Dewi Nashri; Wijaya, M. Sayid (Universitas Islam Negeri Raden Intan Lampung, 2016)
Writing is very important because writing is skill in which we express ideas, feelings, and thought in written form. The students’ writing ability of SMAN 2 Bandar Lampung is still low especially in writing narrative text. Storyboard is applied to solve this problem. Storyboard is one of planning techniques that encourage learners to think creatively and critically by visualizing the story they are going to write in sequence. The objective of this research is to know whether there is an Influence of Using Storyboard Towards Students’ Narrative Text Writing Ability at the Second Semester in the Tenth Grade of SMAN 2 Bandar Lampung in the Academic Year of 2015/2016. The research methodology used was quasi experimental design. In collecting the data, the writer used instrument of writing test. Based on the data analysis, it was found that the result of the data analysis computed by using SPSS was Sig 0.047 and ? = 0.05. It means Ha is accepted because Sig < α = 0.05. Therefore, there is a significant influence of using storyboard towards students’ narrative text writing ability at the second semester in the tenth grade of SMAN 2 Bandar Lampung in the academic year of 2015/2016.